2007
DOI: 10.1097/mog.0b013e3280287a0f
|View full text |Cite
|
Sign up to set email alerts
|

Complications related to feeding tube placement

Abstract: Complications related to malpositioned feeding tubes are usually preventable. Poor reporting of feeding tube placement errors hinders the adoption of effective protocols to prevent such errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
125
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(127 citation statements)
references
References 41 publications
0
125
1
1
Order By: Relevance
“…The procedures of insertion, maintenance, and administration of therapy through NET are not exempt from risks. The positioning of the distal tip of the tube in an inadequate anatomical place can cause serious incidents or adverse events (5) , such as the infusion of diet or medications into the respiratory tract (6)(7) . Barrier measures, such as checking prescription data, identification of the patient and of the therapeutic composition, access pathway to the gastrointestinal tract (GIT), and the performance of X-rays (XR) for the confirmation of tube positioning are actions indicated to prevent complications (1)(2) .…”
Section: Introductionmentioning
confidence: 99%
“…The procedures of insertion, maintenance, and administration of therapy through NET are not exempt from risks. The positioning of the distal tip of the tube in an inadequate anatomical place can cause serious incidents or adverse events (5) , such as the infusion of diet or medications into the respiratory tract (6)(7) . Barrier measures, such as checking prescription data, identification of the patient and of the therapeutic composition, access pathway to the gastrointestinal tract (GIT), and the performance of X-rays (XR) for the confirmation of tube positioning are actions indicated to prevent complications (1)(2) .…”
Section: Introductionmentioning
confidence: 99%
“…Various theories have been proposed describing the etiology and prognosis but it still remains obscure [1][2][3]5]. Congenital absence of gastric musculature [6,8], high gastric acid production [9], abdominal trauma [7,10], and other associated gastrointestinal conditions like ischemic bowel, necrotising enterocolitis (NEC), intestinal malrotation, duodenal web, hiatus hernia, Meckel's diverticulum, and gastroschisis have all been proposed as possible causes of NGP [3,[11][12][13][14]. Few authors have reported that gastric perforation was seen in the setting of a distal mechanical obstruction [3,5,15].…”
Section: Discussionmentioning
confidence: 99%
“…The inadvertent placement of a gastric tube in the trachea contributes most substantially to the morbidities associated with tube misplacement, including instillation of food into the trachea, tracheal perforation, pneumothorax, and pulmonary hemorrhage. [18][19][20][21] Factors associated with errors in enteral tube placement in children include younger age, decreased level of consciousness, abdominal distention, presence of emesis, and the use of the orogastric route. 1 The EA di waveforms can immediately notify the clinician that the tube is not in the esophagus/stomach and may be in the trachea.…”
Section: Discussionmentioning
confidence: 99%